At the crossroads: Integrative Radiation Oncology in Australia. Issue 1 (April 2018) - Hunter, Darren; Anderson, Nigel
Abstract: Integrative Oncology is an emerging field internationally that aims to amalgamate evidence-based complementary therapies with mainstream medical practices. This editorial outlines the key issues surrounding the development of Integrative Oncology for Australian cancer patients undergoing radiotherapy. Further discussion considers current research for the efficacy of concurrent CAM in the setting of radiotherapy and the numerous obstacles to a truly integrative model of cancer care in Australia; including financial/research limitations and clinician acceptance.